Contrastive Analysis of Noun Phrase in English and Indonesian on Report Text “Camel” from Developing English Competencies Textbook - Ambarita, Mei Isabella; Hutahaean, Selly Wanti; Munthe, Widhi Sofie; Kartika, Dewi; Sitanggang, Anita (International Journal Corner of Educational Research, 2023)
This research aims to discover the similarity and differences of Noun Phrase (NP) used in English and Indonesian sentences. This scientific writing used an instrument of report text as the reference to collect data. The report text was taken from a textbook of Developing English Competencies for senior high school. This research demonstrated that when English Noun Phrase was translated to Indonesian, there were changes in syntatic pattern, syntatic category, and meaning. Based on the research results, researchers found several similarities between Indonesian and English Noun Phrases. Similar parts, including head, determiner,and modifier, formed the Noun Phrase. However, there were also differences between them. English Noun Phrase was frequently expanded to the side of the head; meanwhile, in Indonesian, it was expanded to the back of the head. English Noun Phrase consists of a central-determiner (the, a, an); meanwhile, Indonesian Noun Phrase lacks it.